WHOPPA Enables Parallel Assessment of Leucine-Rich Repeat Kinase 2 and Glucocerebrosidase Enzymatic Activity in Parkinson’s Disease Monocytes - Wallings, Rebecca L.; Hughes, Laura P.; Staley, Hannah A.; Simon, Zachary D.; McFarland, Nikolaus R.; Alcalay, Roy N.; Garrido, Alicia; Martí, María José; Sarró, Eduardo Tolosa; Dzamko, Nicolas; Tansey, Malú Gámez (Frontiers in Cellular Neuroscience, 2022)
Both leucine-rich repeat kinase 2 (LRRK2) and glucocerebrosidase (GCase) are promising targets for the treatment of Parkinson’s disease (PD). Evidence suggests that both proteins are involved in biological pathways involving the lysosome. However, studies to date have largely investigated the enzymes in isolation and any relationship between LRRK2 and GCase remains unclear. Both enzymes are highly expressed in peripheral blood monocytes and have been implicated in immune function and inflammation. To facilitate the standardized measurement of these readouts in large cohorts of samples collected from persons with PD across the globe, we developed and optimized a sample collection and processing protocol with parallel flow cytometry assays. Assay parameters were first optimized using healthy control peripheral blood mononuclear cells (PBMCs), and then LRRK2 and GCase activities were measured in immune cells from persons with idiopathic PD (iPD). We tested the ability of this protocol to deliver similar results across institutes across the globe, and named this protocol the Wallings-Hughes Optimized Protocol for PBMC Assessment (WHOPPA). In the application of this protocol, we found increased LRRK2 levels and stimulation-dependent enzymatic activity, and decreased GBA index in classical iPD monocytes, as well as increased cytokine release in PD PBMCs. WHOPPA also demonstrated a strong positive correlation between LRRK2 levels, pRab10 and HLA-DR in classical monocytes from subjects with iPD. These data support a role for the global use of WHOPPA and expression levels of these two PD-associated proteins in immune responses, and provide a robust assay to determine if LRRK2 and GCase activities in monocytes have potential utility as reliable and reproducible biomarkers of disease in larger cohorts of subjects with PD.